Implementing Advanced HIV Disease Care for Inpatients in a Referral Hospital in Malawi - Demand, Results and Cost Implications - Tom Heller; Douglas Damba; Tapiwa Kumwenda; Jacqueline Huwa; Christine Kamamia; Angellina Nhlema; Claudia Wallrauch; Chimwemwe Chawinga; Cecilia Kanyama; Lillian Gondwe-Chunda; Jonathan Ngoma; Beatrice Matanje; et al. (Ubiquity Press, 2022)
Setting: 100 bed medical ward in referral hospital, Lilongwe, Malawi. Objective: HIV positive patients admitted to hospital often have advanced HIV disease (AHD) and are at risk for mortality. WHO guidelines suggest a package of care for AHD; these are often not implemented, especially in inpatient settings. We describe an implementation model for AHD care, its outcomes in routine care and provide cost estimates. Design: An "AHD care room" was established staffed by HIV counselor, nurse, and clinical officer allowing Provider Initiated Testing and Counseling, diagnostic testing for AHD and ensuring availability of HIV and TB drugs for rapid treatment initiation. Results: In the observation period from January to December 2020, a total of 1549 medical inpatients were tested for HIV (coverage 77.1%); 69 tested positive (yield 4.5%). The total proportion of HIV positive was 32.3% (638 already on ART and 69 newly diagnosed). CD4+ testing was done in 460 medical inpatients (65.1%); 245 (53.2%) were below 200 cells/ml and thus met definition of AHD. A total of 238 received S-CrAg tests; 39 (16.3%) were positive; 62 (28.3%) of 219 U-LAM tests were positive. The cost per identification of HIV positive patient was US$ 110.8; per AHD diagnosis between US$ 17.1 to 78.9; per positive S-CrAg test US$ 18.5 and per positive U-LAM test US$ 17.5. Conclusion: Our model successfully implemented AHD services according to WHO guidelines and provides basic costing data. Similar services could be implemented in other hospitals in LMICs.